PENGARUH INOVASI PRODUK, BRAND IMAGE DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN ( STUDI KASUS TERHADAP KONSUMEN SCARLETT WHITENING SURAKARTA ) - Rizka Indiswari Ramadhani; Sudarwati Sudarwati; Raisa Aribatul Hamidah (JURNAL ILMIAH EDUNOMIKA, 2022)
Along with the development of competition in the skin care industry in the commercial world, many companies take advantage of opportunities to create new changes for new businesses, the role of innovation, brand image and brand ambassador is expected to help companies win the competition and create good value in the eyes of consumers. This study aims to determine the effect of Product Innovation, Brand Image and Brand Ambassador on Purchase Decisions on Scarlett Whitening Products in Surakarta City. The approach used is a quantitative approach. The population is consumers who have used the Scarlett Whitening product twice, while the sample used is 100 respondents using purposive sampling technique. The results of research on Product Innovation, Brand Image, Brand Ambassador each have a positive and significant effect on Decision Making for Purchasing Scarlett Whitening Products in Surakarta City. Keywords: Purchase Decision, Product Innovation, Brand Image, Brand Ambassador,